Aethonium as an effective solubilizing agent for water in an organic solvent - Kamneva, N.N.; Mchedlov-Petrossyan, N. O.; Kalchenko, V. I. (Reports of the National Academy of Sciences of Ukraine, 2014)
It has been revealed that the cationic surfactant Aethonium, 1,2-ethylene-bis-(N-decyloxycarbonylmethyl-N,N-dimethylammonium) dichloride, is able to solubilize water in trichloromethane without any co-surfactant additions. The W value, i. e., the water: surfactant ratio reaches the value of 40–50, with the average nanodroplet diameter of about 10 nm, which is quite atypical of reversed cationic surfactant-based ternary microemulsions. The possibility to determine the apparent ionization constants of indicators in Aethonium-solubilized nanoscopic water has been demonstrated.